Passing the buck - Friedel Bolle (European University Viadrina, Department of Business Administration and Economics, 2011)
Shifting the responsibility for a necessary but costly action to someone else is often called Passing the Buck. Examples of such behavior in politics are environmental and budget problems which are left to future generations. Small group examples are (not) washing the dishes or (not) dealing with a difficult customer. Under the assumption of altruistic preferences, rational behavior in this game is derived and confronted with experimental data. By comparison, the sequence of possible decision makers in the normal Passing the Buck game is substituted with an expert who alone is competent to fix the problem. It turned out that the marginal probabilities of shifting the responsibility are in good accordance with the theoretical model, although with completely different parameter distributions for experts and non-experts. The structure of the individual decisions, however, is best described by a random parameter model (Cox et al., 2007).
Keywords: 330; public goods; volunteer's dilemma; responsibility